A norma linguística oitocentista em construção na/da correspondência do governador Paulo José da Silva Gama - Moreira, Leici Landherr (2024)
This research aims to describe the emerging nineteenth-century linguistic norm as it takes shape in the manuscript correspondence sent by Paulo José da Silva Gama, governor of the Captaincy of Rio Grande de São Pedro from 1803 to 1809. We hypothesize that the governor’s correspondence signals a linguistic norm on the brink of consolidation, shaped by both prescriptive language norms and actual language practices within the administrative context. To investigate this, we examine consistent indicators of linguistic phenomena within the governor’s correspondence, linked to sociohistorical variables, based on Coseriu’s concept of linguistic norm (1980, 1989) and the theoretical-methodological framework of Historical Sociolinguistics. The research corpus includes 113 manuscripts from Gama’s correspondence, housed in the Overseas Historical Archive and the Historical Archive of Rio Grande do Sul. These documents consist of multiple originals (first, second, and third copies) and heterographic copies of letters and official dispatches addressed to the Secretary of the Navy and Overseas, João Rodrigues de Sá e Melo, later Viscount of Anadia, and to Prince Regent D. João VI, spanning from 1803 to 1807. After producing a semi-diplomatic edition of these manuscripts, we analyzed occurrences of terms or expressions that referenced language or indicated a prescriptive context as opposed to a usage context, alongside etymological and phonological graphic variants in correlation with sociohistorical variables (e.g., scribe, recipient, document type, and documentary tradition). The findings show that shared linguistic phenomena among scribes in these documents reappear in written records from the nineteenth and early twentieth centuries in Rio Grande do Sul. Thus, the characterization of the nineteenth-century norm as it develops in the governor’s correspondence begins to reflect local features of the Portuguese spoken in Rio Grande de São Pedro while also highlighting a tension between the prescriptive norms advocated by the governor and the linguistic variation observed in the corpus documents.